Electronic structure and optical properties of the dialkali metal monotelluride compounds: Ab initio study - Souadia, Z.; Bouhemadou, Abdelmadjid; Bin-Omran, Saad; Khenata, Rabah; Al-Douri, Yarub; Al Essa, S. (Elsevier, 2019)
Structural parameters, electronic structure and optical properties of the dialkali metal monotelluride M 2 Te (M = Li, Na, K and Rb) compounds in the cubic antifluorite structure were investigated via ab initio calculations using the all electron linearized augmented plane wave approach based on density functional theory with and without including spin-orbit coupling (SOC). The exchange-correlation interactions were described within the PBEsol version of the generalized gradient approximation and Tran-Blaha modified Becke–Johnson potential (TB-mBJ). Optimized equilibrium lattice parameters are in excellent accordance with existing measured ones. Computed energy band dispersions show that the studied compounds are large band gap materials. Inclusion of SOC reduces the band gap value compared to the corresponding one calculated without including SOC. Determination of the energy band character and interatomic bonding nature are performed using the densities of states diagrams and charge density distribution map. Linear optical function spectra are predicted for a wide energy range and the origin of the dielectric function spectrum peaks are determined. © 2019 Elsevier Inc.